2020
DOI: 10.1093/cdn/nzaa063_093
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight and Obesity Among Adult Women in China, Mali and United States: Evolution of Trends over Ten Years

Abstract: Objectives This article assessed trends in the prevalence of overweight and obesity over ten years among adult women. Methods A cross-sectional study was conducted using National Surveys Data from China, Mali and the United States between 2001–2002 and 2012–2013. The sample population consisted of all adult women: 140,022 (2002) and 157,850 (2012) adults aged 18 and above in China, 10,424 (2002) and 4502 (2012) women aged 15–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…First, factors associated with overweight and obesity are yet to be assessed in Mali, despite a report that, in 2001, 10% of women in Bamako were obese. 26 , 27 Also, Traore et al 28 examined the trends of overweight and obesity among adult women in China, Mali and the USA and found that overweight in Mali has increased from 11.2% to 12.9% between 2002 and 2012—an increase of 1.7%. This increase was greater than that recorded in the USA (1.5%) but the growth was less than that recorded in China (7.2%).…”
Section: Introductionmentioning
confidence: 99%
“…First, factors associated with overweight and obesity are yet to be assessed in Mali, despite a report that, in 2001, 10% of women in Bamako were obese. 26 , 27 Also, Traore et al 28 examined the trends of overweight and obesity among adult women in China, Mali and the USA and found that overweight in Mali has increased from 11.2% to 12.9% between 2002 and 2012—an increase of 1.7%. This increase was greater than that recorded in the USA (1.5%) but the growth was less than that recorded in China (7.2%).…”
Section: Introductionmentioning
confidence: 99%